THE FEATURES OF GENDER STEREOTYPES OF THE PERSONALITY OF MILITARY WOMAN IN THE CONDITIONS OF ANTI-TERRORIST OPERATION, JOINT FORCES OPERATION - Slipushko, Galyna (PSYCHOLOGICAL JOURNAL, 2019)
The problem of the gender stereotypes of military woman in the conditions of Anti-terrorist operation and Joint Forces Operation, in particular in the conditions of active military actions, is relevant to modern psychological science. This issue is integrated into global gender studies, when it is important to take into account the interests of women in the formation of the armed forces, the army of any state. In a modern democratic society, the equal rights of women and men in all areas of life, in particular in the Armed Forces of Ukraine, must be maximally ensured. In Ukraine gender equality is proclaimed by the Constitution of Ukraine, the Labor Code, the Law of Ukraine "On Equal Rights and Opportunities for Women and Men", etc. The common negative stereotype is the idea of the limited role of woman in the Armed Forces of Ukraine, the impossibility to occupy important positions by her. Instead, in real life, it is quite different, so this stereotype contradicts the real life position of women. Also there is a stereotype about the impossibility of women to realize themselves on equal principles and rights with men in the zone of Anti-terrorist operation and Joint Forces Operation. This is due to the fact, that there are many social, cultural, legal, educational barriers on the way of women to the traditionally "male" positions in the armed forces, Anti-terrorist operation and Joint Forces Operation. Also there is a stereotype about the impossibility of military women to occupy certain positions. Instead, in practice, they occupy these positions quite successfully, fulfilling all necessary functions. By this time, the effect of the stereotype about the impossibility of women to do certain types of work, which are called "difficult", is rather strong. Instead, as practical life convinces, in the zone of Anti-terrorist operation and Joint Forces Operation, military women very often do such types of work very successfully. Therefore, nowadays in Ukraine, in particular in its armed forces, in the area of active military actions, we observe an active overcoming of those gender stereotypes, which are determined by the active positions of women in this regard. It is relevant and important for the modern Ukrainian psychological science to realize that the rights and possibilities of a person, declared in the legislation, are systematically violated and not followed in the present society. Therefore, we have the facts of gender discrimination. The most clearly this is manifested in the conditions of women’s staying in the zone of active military actions, in Anti-terrorist operation and Joint Forces Operation. The defining and expressive feature of European democratic development of society is the respectful observance and development of gender parity in the Armed Forces of Ukraine. The determinative and expressive feature of European democratic development of society is the respectful abidance and development of gender parity in the Armed Forces of Ukraine. The traditional idea of ​​the role of a woman with limited social and professional roles completely contradicts her real life position. The stereotype about the impossibility of women to realize themselves professionally on equal principles and rights with men is established in the zone of ​​active military actions, in zones of Anti-terrorist operation and Joint Forces Operation. This is due to the fact, that there are many moral, cultural, legal, educational, social obstacles and barriers on the way of women to the traditionally "male" positions in the armed forces, their real role in the zone of Anti-terrorist operation and Joint Forces Operation. Also there is a rather strong stereotype about the impossibility of military women to occupy certain positions in the armed forces. Instead, in real life, practical activity they fulfill such functions successfully. Very often more successfully than men. In addition, the presence of women on military positions contributes to the development of humanity and empathy in the armed forces. It is emphasized in many gender studies. The stereotype about the impossibility of women to do certain types of work, which are called "difficult", is common too. Although in practical life military women very often do such types of work very effectively in the zone of Anti-terrorist operation and Joint Forces Operation. In general, in modern Ukraine, in particular its armed forces, in the zone of Anti-terrorist operation and Joint Forces Operation, during the last five years we observe the process of a substantive overcoming of gender stereotypes. This is the result of women`s active positions in this gender issue.